2015
DOI: 10.2147/iprp.s64535
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in pediatric patients and opportunities for pharmacists' involvement

Abstract: Rates of chronic conditions among pediatrics have been steadily increasing and medications used to treat these conditions have also shown a proportional increase. Most clinical trials focus on the safety of solitary medications in adult patients. However, data from these trials are often times extrapolated for use in pediatric patients who have different pharmacokinetic processes and physical profiles. As research increases and more drugs become available for pediatric use, the issue of polypharmacy becomes mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 59 publications
1
26
0
1
Order By: Relevance
“…Pediatric polypharmacy is the term used to describe children taking more than one medication . Literature has shown that the prevalence of polypharmacy is on the rise for both adults and chidren . While the full implications of polypharmacy are unknown, polypharmacy has been linked to an increase in adverse drug reactions, potential drug‐drug interactions, hospital readmissions, and medical costs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric polypharmacy is the term used to describe children taking more than one medication . Literature has shown that the prevalence of polypharmacy is on the rise for both adults and chidren . While the full implications of polypharmacy are unknown, polypharmacy has been linked to an increase in adverse drug reactions, potential drug‐drug interactions, hospital readmissions, and medical costs .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Literature has shown that the prevalence of polypharmacy is on the rise for both adults and chidren. 3,4 While the full implications of polypharmacy are unknown, polypharmacy has been linked to an increase in adverse drug reactions, 5 potential drug-drug interactions, 6 hospital readmissions, 7 and medical costs. 8 The observed prevalence of pediatric polypharmacy depends on patient characteristics, contextual, and study design factors.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to multiple medications is common among pediatric patients in both inpatient and outpatient settings [ 1 4 ]. Using multiple medications can have benefits such as augmentation, tolerability, and efficacy [ 5 – 7 ], or harms such as adverse drug reactions, drug-drug interactions, difficulty adhering to complex regimens, toxicity, overdose, and increased cost [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Дети с тяжелыми хроническими заболеваниями, такими как астма, эпилепсия или муковисцидоз, получают несколько препаратов одновременно согласно существующим клиническим рекомендациям по ведению таких пациентов: например, пациентам с муковисцидозом могут назначаться панкреатические ферменты, поливитамины, антибиотики, противовоспалительные средства, бронхо-и муколитики [19]. Хотя эти пациенты будут получать комбинированную терапию практически постоянно, данные схемы лечения документируются соответствующим образом и отслеживаются для оптимального управления заболеванием [20].…”
Section: факторы риска полипрагмазииunclassified